Analysis of various factors on the relapse of acute neurological attacks in Behçet's disease. Issue 6 (November 2014) - Hirohata, Shunsei; Kikuchi, Hirotoshi; Sawada, Tetsuji; Nagafuchi, Hiroko; Kuwana, Masataka; Takeno, Mitsuhiro; Ishigatsubo, Yoshiaki
Abstract Objectives. To investigate the influences of various factors on the relapse of acute neurological attacks in patients with Behçet's disease (BD). Methods. Sixty-one patients, who met the international classification criteria for BD, had attacks of acute neuro-Behçet's disease (NBD) and could be followed up at least for 2 months, including 60 patients in our multicenter retrospective survey on BD patients in 2011. The factors associated with relapse of acute neurological attacks were assessed. Results. Twenty-one of 61 patients had been taking cyclosporine A (CyA) at the onset of acute NBD. All the 21 patients with CyA and 33 of the 40 patients without CyA had eye involvement. There were no significant differences in demographic features, clinical symptoms, MRI findings, the need for, and responses to corticosteroid therapy including pulse therapy between patients with CyA and those without CyA. CyA was withdrawn in 19 of 21 patients with CyA. Of note, patients with CyA showed significantly lower relapse rates than those without CyA (HR 0.1283, 95% CI: 0.0788–0.7836, p = 0.0186 as calculated by log-rank test). Moreover, colchicine was found to reduce the relapse rates in patients with acute NBD without CyA (HR 0.2771, 95% CI: 0.0827–0.9422, p = 0.0450 [log-rank test]). Conclusion. These results indicate that CyA-related acute neurological manifestations are almost identical with CyA-unrelated acute events of NBD, except for the paucity of relapse on withdrawal of CyA. The data also demonstrate that colchicine is effective to prevent relapses of acute neurological attacks especially in patients with CyA-unrelated acute NBD.